THE ROLE AND OBJECTIVES OF PRIMARY HEALTH CARE SERVICES DUE TO GENDER- AND AGERELATED FEATURES OF HIV INFECTION IN TAJIKISTAN - D.A. KADYROVA; S.S. KARIMOV; N.A. ABDUKHAMEDOV (Avicenna Tajik State Medical University, 2019)
Objective: Proposing an effective measures of counteraction to HIV infection due to its gender-age characteristics in Tajikistan Methods: A comparative analysis of official quantitative statistics on HIV infection by the Ministry of Health and Social Protection of the Republic of Tajikistan, the materials of international conferences on HIV infection, publications by WHO and UNAIDS, etc Results: In Tajikistan, 1,207 new HIV cases (adults, children) were reported in 2017, most of them in reproductive age, representatives of key populations, labor migrants, pregnant women and others. The main, progressing route of HIV transmission is a sexual one (66%). The number of people living with HIV (PLWH) as of January 1, 2018, was 7,556, most of whom were of reproductive age and with an increasing proportion of women among them. About 70% of PLWHs receive treatment against HIV, an antiretroviral therapy that is prescribed for the first time in 2017 to 1,243 patients, many of them immediately after being diagnosed with HIV. According to routine monitoring of viral load to assess the effectiveness of treatment, almost 70% of patients have suppression of HIV. Conclusion: In Tajikistan, the registration of new HIV cases is increasing, and the number of HIV recipients receiving HIV treatment. Primary health care needs to strengthen HIV education among the population, improve the availability of voluntary HIV testing for people at risk of infection, to cover HIV testing of all patients for clinical reasons and all pregnant women.